Science, Innovation and National Growth - Thomas Brenner (Philipps-University Marburg, Department of Geography, 2014)
This paper studies the effects of public research (publications) and innovation output (patents) on national economic growth with the help of a GMM panel regression including 114 countries. Effects on productivity growth and capital and labor inputs are distinguished. Furthermore, different time lags are examined for the various analyzed effects and two time periods as well as less and more developed countries are studied separately. The results confirm the effect of innovation output on productivity for more developed countries. Simultaneously, innovation output is found to have negative impacts on capital and labor inputs, while public research is found to have positive impacts on labor inputs.
Keywords: O11; O31; E10; C23; 330; national growth; innovation; public research; growth